Model for assessing the spatial-functional quality of an apartment - Alfirević, Đorđe; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2026)
This paper addresses the development of a model for assessing the spatial-functional quality of an apartment, with the aim of establishing an operationally applicable and comparable framework for the evaluation of housing solutions. The methodological approach is based on the interpretation and simplification of existing theoretical models, translating them into a structured assessment system organised into four segments: spatial conditions for the performance of functions, functional compatibility, dimensional and regulatory adequacy, and the flexibility and lifespan of the apartment. Each segment is elaborated through a set of clearly defined criteria that enable a systematic consideration of different aspects of spatial organisation and their interrelationships, including potential conflicts in the use of space. The assessment is conducted using a three-level scale and the aggregation of results into a single quality indicator, ensuring quantification and comparability across different housing solutions. The model is grounded in the assumption that housing quality can be understood through the conditions for the performance of activities and their spatial relationships, with emphasis placed on organisational rather than exclusively regulatory aspects. Application of the model to a specific case indicates its capacity to differentiate levels of spatial-functional quality and to identify spatial limitations through quantified indicators, with the results serving an illustrative purpose as a demonstration of the model’s application. The proposed approach enables a transparent and systematised assessment while maintaining operational simplicity and a clearly defined evaluation structure. In conclusion, the developed model represents a methodologically grounded framework that connects theoretical principles of residential spatial organisation with a concrete evaluation procedure, with potential for further development and application in both design and evaluative practice.
Keywords: spatial-functional quality; housing; evaluation model; apartment organisation; flexibility of residential space